2015
DOI: 10.1007/s11064-015-1694-y
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotection of Ischemic Preconditioning is Mediated by Anti-inflammatory, Not Pro-inflammatory, Cytokines in the Gerbil Hippocampus Induced by a Subsequent Lethal Transient Cerebral Ischemia

Abstract: Ischemic preconditioning (IPC) induced by sublethal transient cerebral ischemia could reduce neuronal damage/death following a subsequent lethal transient cerebral ischemia. We, in this study, compared expressions of interleukin (IL)-2 and tumor necrosis factor (TNF)-α as pro-inflammatory cytokines, and IL-4 and IL-13 as anti-inflammatory cytokines in the gerbil hippocampal CA1 region between animals with lethal ischemia and ones with IPC followed by lethal ischemia. In the animals with lethal ischemia, pyrami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…Since the brain is well known to be an aseptic organ, and pathogens are not involved in the neuroinflammatory response following ischemia-reperfusion injury, some studies call this response a “sterile inflammatory response” [ 46 , 48 ]. In addition, neuroinflammation is concerned with both beneficial and detrimental roles in ischemic brains, and these are modulated by anti- and pro-inflammatory cytokines [ 49 , 50 , 51 ]. It is well known that pro-inflammatory cytokines exacerbate and advance deleterious inflammatory processes, but anti-inflammatory cytokines suppress the expressions of pro-inflammatory cytokines and bring advantageous inflammatory processes in ischemic brains [ 10 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since the brain is well known to be an aseptic organ, and pathogens are not involved in the neuroinflammatory response following ischemia-reperfusion injury, some studies call this response a “sterile inflammatory response” [ 46 , 48 ]. In addition, neuroinflammation is concerned with both beneficial and detrimental roles in ischemic brains, and these are modulated by anti- and pro-inflammatory cytokines [ 49 , 50 , 51 ]. It is well known that pro-inflammatory cytokines exacerbate and advance deleterious inflammatory processes, but anti-inflammatory cytokines suppress the expressions of pro-inflammatory cytokines and bring advantageous inflammatory processes in ischemic brains [ 10 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported (6,29) that pyramidal cells of the stratum pyramidale in the hippocampal CA1 region die several days following transient cerebral ischemia. Mongolian gerbils have been generally used as a good experimental animal model of transient cerebral ischemia as the posterior communicating arteries in Willis' circle, which connect the vertebrabasilar and carotid arterial system, are lacking in gerbils and transient cerebral ischemia can easily be made by the ligation of bilateral common carotid arteries (24,30,31). …”
Section: Discussionmentioning
confidence: 99%
“…As previously described (24), gerbils (n=7 at each time point in each group) were anesthetized with pentobarbital sodium at the designated times and perfused transcardially with 0.1 M phosphate-buffered saline (pH 7.4) followed by 4% paraformaldehyde in 0.1 M phosphate-buffer (PB; pH 7.4). The brains were removed and postfixed in the same fixative for 6 h, and the brain tissues were sectioned on a cryostat (Leica Microsystems GmbH, Wetzlar, Germany) into 30 µm coronal sections.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…"mong the activated mechanisms are an increase in anti-inlammatory cytokines such as IL-4 and IL-13 that ease hippocampal pyramidal neuron survival after an ischemic event in gerbils [90]. Tu XK and his team also demonstrated that neuroprotection can be originated by pre-conditioning through modulation of the phosphatidyl inositol 3-kinase PI3K/"kt and ERK1/2 pathway modulation [91] CD3, CD8 T cells.…”
Section: Modulation Of Immune Response As a Therapy For Strokementioning
confidence: 99%